Analisis Kebutuhan Modal Kerja Dan Keuntungan Kontraktor Berdasarkan Sistem Pembayaran Pada Peningkatan Struktur Jalan Kedungdung–Bringkoning Kabupaten Sampang - Zabadi, Fairus; Yuwana, Wahyu (Faculty Of Engineering University 17 August 1945 Semarang, 2024)
The working capital of construction work contractors is very influential in expediting the implementation of construction work and being able to meet work time scheduling targets. To gain profits, contractors must be able to manage existing resources. This research aims to determine working capital needs, profits and effectiveness. This type of research uses descriptive qualitative. Research data sources were obtained from secondary data and primary data. Data collection was obtained from library observations, interviews, observations and document studies. The data analysis used is based on the MC (Montly Certificate), Termin (Termyn Payment) and Final (Turnkey Payment) payment systems with several policy options, namely Source of contractor capital, Down payment, and Bank loan. The results of the analysis obtained are, Working capital requirements based on MC with Contractor Capital Resources IDR 3,000,000,000 and profit IDR 2,245,689,086, Down Payment IDR 2,963,637,000 and profit IDR 2,245,689,086, Bank Loan IDR 5,400,000,000 and profit IDR 2,072,889,086. Working capital requirements based on Terms with Contractor Capital Source IDR 3,000,000,000 and profit IDR 2,245,689,086, Down Payment IDR 2,963,637,000 and profit IDR 2,245,689,086, Bank Loan IDR 2,800,000,000 and profit IDR 2,156,089,086 . Working capital requirements based on End with Contractor Capital Source IDR 3,000,000,000 + Loan IDR 3,600,000,000 and profit IDR 2,130,489,086, Bank Loan IDR 6,550,000,000 and profit IDR 2,036,089,086. The highest percentage of capital effectiveness and profits is the Termin payment system with the bank loan option, 77%.